Interval cancers in a population-based screening program for colorectal cancer with gender-specific cut-off levels for fecal immunochemical test. (September 2022) - Ribbing Wilén, Hanna; Saraste, Deborah; Blom, Johannes
Objective: To evaluate interval cancers (IC) in the population-based Swedish regional colorectal cancer (CRC) screening program of Stockholm-Gotland, which uses gender-specific cut-off levels for the fecal immunochemical test (FIT). Methods: All individuals aged 60–69 in Stockholm-Gotland invited to the screening program in October 2015 to September 2017 were followed up 2 years after invitation. Cut-off level for a positive FIT was 40 µg/g in women and 80 µg/g in men. Those with a positive FIT were referred to colonoscopy. Screening-detected CRC (SD-CRC) and IC after negative FIT (FIT-IC) or negative screening colonoscopy (Colonoscopy-IC) were identified in the Swedish colorectal cancer register. The IC rate was calculated as IC/(FIT negatives + negative screening colonoscopies). The IC incidence rate (ICs among negatives per 100, 000 person-years) in different sex and age groups was compared to the mean CRC incidence before regional screening implementation. Test sensitivity was defined as SD-CRC/(SD-CRC + FIT-IC). Results: Approximately 214, 400 individuals were invited, and in 3521 screening colonoscopies 257(6.3%) SD-CRCs were detected. During follow-up, 124 FIT-IC and 7 Colonoscopy-IC were diagnosed, yielding an IC rate of 12.6 and 6.0 per 10, 000 negatives ( p  = 0.00005) and a test sensitivity of 62% and 75% ( p  = 0.01) in men and women respectively. The IC incidence rate compared to CRC incidence was non-significantly lower in women. Conclusion: In the population-based screening program of Stockholm-Gotland with a cut-off of 40 µg/g in women and 80 µg/g in men, the test sensitivity was higher and the IC rate was lower in women, which might imply lowering the cut-off level in men. However, the IC incidence rate relative to the CRC incidence was similar in both genders.